2006
DOI: 10.1016/s1472-6483(10)61081-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone: clinical insights into a promising biomarker of ovarian follicular status

Abstract: In contrast to most hormonal biomarkers of the follicular status, anti-Müllerian hormone (AMH) is exclusively produced by the granulosa cells of a wide range of follicles (primary to the early antral stages), presumably FSH-independently and with little susceptibility to disorders of antral follicle growth during the luteal-follicular transition. This paper summarizes the authors' clinical research on the role of AMH as a marker of ovarian functioning. It shows that the relationship between antral follicle cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 45 publications
2
54
0
3
Order By: Relevance
“…The concentration of AMH is higher in the small antral follicles than in the preovulatory follicles, suggesting that the circulating AMH levels reflect both the quantity and the quality of the remaining follicles [7]. Since, there is no change in the AMH levels in response to the gonodatrophins, it can be measured throughout the cycle in contrast to the other hormones-the AMH intracycle and the cycle to cycle variation is also negligible.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of AMH is higher in the small antral follicles than in the preovulatory follicles, suggesting that the circulating AMH levels reflect both the quantity and the quality of the remaining follicles [7]. Since, there is no change in the AMH levels in response to the gonodatrophins, it can be measured throughout the cycle in contrast to the other hormones-the AMH intracycle and the cycle to cycle variation is also negligible.…”
Section: Resultsmentioning
confidence: 99%
“…This positive correlation is confirmed by other researchers too. 11,12 Despite the fact, that at present there is no agreement on identification of the antral follicles by size, the majority of researchers imply the amount of 2-10 mm follicles counted in early follicular phase. 13,14 It has been reported that human antral follicles measuring <6 mm express the great amount of AMH, and levels decline with antral follicles increase in size.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the following indicators, markers, and tests are used to assess ovarian reserve: age, sex hormones (basal FSH, LH, and E2 levels), INHB, Mullerian duct antihormone levels, ovarian volume, and blood flow, clomiphene citrate challenge test (CCCT) and gonadotropin-releasing hormone agonist stimulation test (Vladimirov et al, 2005;Feyerisen et al, 2006;Dehghani-Firouzabadi et al, 2008;Busacca and Vignali, 2009).…”
Section: Discussionmentioning
confidence: 99%